An evaluation on the role of microfinance institutions as an instrument for poverty reduction strategy in Semporna, Sabah - Ibrahim, Mohd Romzee; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Faculty of Forestry, Universiti Putra Malaysia, 2013)
The purpose of this paper is to evaluate the role of microfinance institutions (MFIs) as an instrument and strategy for poverty reduction in Semporna. The motivation is to improve the society in rural areas who were declined to obtain any financial aids from commercial financial institutions. Sabah is the poorest state in Malaysia, without the exception of Semporna, which is one of the poorest rural districts. This incidence of poverty level reported by the Department of Statistics Malaysia is coupled with its potential of becoming the tourism destination hub, indicates that the communities are not utilizing various financial aids available to help them to escape from their state of poverty level. Two microfinance institutions, namely Yayasan Usaha Maju (YUM) and Tekun Nasional (TEKUN) are selected; to evaluate their roles in funding and creating the awareness amongst the communities. The list of participants will be obtained from these institutions and structured interviews as well as collection of data through surveys will be coordinated from both the institutions and the participants of the microfinance program. The findings will formulate a strategy for an establishment of a sustainable microfinance institution, to better serve the poor.